Fatores que afetam a oviposição de Bemisia tabaci (Genn.) biótipo B (Hemiptera: Aleyrodidae) em tomateiro - Toscano, Luciana C. [UNESP]; Boiça Jr., Arlindo L. [UNESP]; Maruyama, Wilson I. [UNESP] (Springer Nature, 2002)
The aim of the present work was to determine the oviposition preference of the silverleaf whitefly on tomato (Lycopersicon esculentum). Preferred plant age and leaflet position on the plant were studied and the number of adults per plant necessary for selecting hosts was determined. Bruna VFN hybrid plants at different ages (30-, 45- and 60-days old) were offered to adult whiteflies in free choice test and 30-day old plants in no-choice test. Leaves were collected from upper and lower part of the plant; the leaflets were divided into three categories: basis (those near the steam of plant), middle and apex (terminal leaflet). The 30-day old plants were more preferred for oviposition in free choice test. In the upper part of the plant, whitefly adults preferred to oviposit on the leaflets at the apex and the middle of the leaves. However, in the lower part of the plant, the basal leaflets were preferred in relation to middle and apex. The densities of 100 or 150 adults per tomato plant were considered adequate for genotypes screening, using no-choice test.
Factors acting on Bemisia tabaci (Genn.) B biotype (Hemiptera: Aleyrodidae) oviposition in tomato
Keywords: Bemisia argentifolii; Insecta; Lycopersicon esculentum; Oviposition preference; Silverleaf whitefly